Pengaruh Diamond Fraud dalam Mendeteksi Fraudulent Financial Reporting pada Perusahaan yang Terdaftar di JII - Rahmi Ambarwati; Ramadhani Irma Tripalupi; Firman Yudhanegara (CV. Kalimasada Group, 2025)
This study is motivated by the inconsistency of findings in previous research on the Fraud Diamond theory, as well as the phenomenon of companies remaining listed in the Jakarta Islamic Index (JII) despite being involved in financial statement manipulation. The objective of this study is to examine the influence of the elements of the Fraud Diamond theory, pressure, opportunity, rationalization, and capability, on the likelihood of fraudulent financial reporting among companies listed in the JII during the 2021–2023 period. Each element is measured using specific proxies: financial target (pressure), ineffective monitoring (opportunity), total accrual (rationalization), and directors change (capability). This research adopts a quantitative approach and employs descriptive statistics, classical assumption tests, panel data regression, multiple linear regression, hypothesis testing, and coefficient of determination (R²) analysis. The results show that, simultaneously, all four elements of the Fraud Diamond have a significant influence on the occurrence of fraudulent financial reporting. However, partially, only pressure and rationalization have a significant effect, while opportunity and capability do not significantly contribute to the detection of fraudulent financial reporting.